2022
DOI: 10.1111/bcp.15323
|View full text |Cite
|
Sign up to set email alerts
|

Increase of high‐risk tramadol use and harmful consequences in France from 2013 to 2018: Evidence from the triangulation of addictovigilance data

Abstract: The aim of this paper is to assess recent developments in non-medical tramadol use, tramadol use disorder, illegal procurement and deaths. Methods: This study used repeated cross-sectional analysis of data collected nationwide from 2013 to 2018. Analysis was conducted through multisource monitoring of the French Addictovigilance Network of: (1) validated reports of high-risk tramadol use, (2) record systems collecting information from toxicology experts investigating analgesic-related deaths (DTA) and deaths r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…45,48 Increasing trends of tramadol use including dependency and consequential impairments to health are published worldwide. [49][50][51] The trend in the United States follows a similar pattern as reported by Mullins et al, 52 who indicate a 70.6% increase in tramadol prescription from emergency department visitations between 2007 and 2018 Mullins et al concluded that overall opioid utilization remained either stable or decreased while tramadol use continued to rise. Recently, tramadol has been associated with an increased risk of all-cause mortality in patients with osteoarthritis, 53 a disconcerting finding given the extent of comorbid joint arthritis observed in our study.…”
Section: Treatment For Clbpsupporting
confidence: 67%
See 1 more Smart Citation
“…45,48 Increasing trends of tramadol use including dependency and consequential impairments to health are published worldwide. [49][50][51] The trend in the United States follows a similar pattern as reported by Mullins et al, 52 who indicate a 70.6% increase in tramadol prescription from emergency department visitations between 2007 and 2018 Mullins et al concluded that overall opioid utilization remained either stable or decreased while tramadol use continued to rise. Recently, tramadol has been associated with an increased risk of all-cause mortality in patients with osteoarthritis, 53 a disconcerting finding given the extent of comorbid joint arthritis observed in our study.…”
Section: Treatment For Clbpsupporting
confidence: 67%
“…However, tramadol is neither a benign substance nor is it non‐addictive as evidenced by its adverse effects, including seizures and various drug interactions 45,48 . Increasing trends of tramadol use including dependency and consequential impairments to health are published worldwide 49–51 . The trend in the United States follows a similar pattern as reported by Mullins et al, 52 who indicate a 70.6% increase in tramadol prescription from emergency department visitations between 2007 and 2018 Mullins et al concluded that overall opioid utilization remained either stable or decreased while tramadol use continued to rise.…”
Section: Discussionmentioning
confidence: 81%
“…In light of the US crisis, the French harm-reduction model, the legal framework for access to strong opioids, and the multimodal approach to pain treatment may prove inspiring . In contrast, our data suggest an increase in tramadol-related deaths, which is consistent with an increase in illegal ways of procurement, high-risk use driven by its psychoactive effects sought to control withdrawal symptoms, and self-medication for anxiety or depressive symptoms …”
Section: Discussionmentioning
confidence: 48%
“…Also, some participants reported that they cannot stop using the drug and they feel tensed if they cannot get their supply. These signs re-echo the fact that craving and continuing use of tramadol can trigger dependency (Dunn et al, 2019;Roussin et al, 2022;Zhang and Liu, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…Tramadol inhibits the re-uptake of noradrenaline and serotonin (Boostani and Derakhshan, 2012) and is thought to have a lower abuse and dependency potential than other opioid analgesics such as morphine, oxycodone, codeine and hydrocodone (Green et al , 2021; Reines et al , 2020; World Health Organization [WHO], 2014). Scholars have shown that the use of opioid analgesics for pain management is complicated by the fact that opioids can produce euphoric effects and are often misused (Dunn et al , 2019; Roussin et al , 2022; Zhang and Liu, 2013).…”
Section: Introductionmentioning
confidence: 99%